2017
DOI: 10.1186/s12906-017-1970-2
|View full text |Cite
|
Sign up to set email alerts
|

A pilot single centre, double blind, placebo controlled, randomized, parallel study of Calmagen® dermaceutical cream and lotion for the topical treatment of tinea and onychomycosis

Abstract: BackgroundMost of the current anti-fungal treatments are chemical-based, fungistatic, have low efficacy in the treatment of tinea and toxicity concerns, while onychomycosis remains recalcitrant to most antifungal therapies. The study aimed to establish the fungicidal, efficacy and safety profile of Calmagen® dermaceutical cream and lotion containing AMYCOT® as a topical treatment in patients with severe to very severe presentations of fungal skin (tinea) and nail infections (onychomycosis).MethodsA randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…One open-label single-arm trial treated participants with Calmagen for 11 months and reported a clinical cure rate of 70% and partial clinical cure rate of 20% [11]. The second double-blind, randomized, controlled clinical trial compared Calmagen lotion to an inert placebo for a 12-week treatment course [13]. Authors found that patients receiving Calmagen achieved a 100% mycological cure rate and an improvement in their clinical severity score compared to the placebo group ( p = 0.0008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One open-label single-arm trial treated participants with Calmagen for 11 months and reported a clinical cure rate of 70% and partial clinical cure rate of 20% [11]. The second double-blind, randomized, controlled clinical trial compared Calmagen lotion to an inert placebo for a 12-week treatment course [13]. Authors found that patients receiving Calmagen achieved a 100% mycological cure rate and an improvement in their clinical severity score compared to the placebo group ( p = 0.0008).…”
Section: Resultsmentioning
confidence: 99%
“…The rest were variations of these two study designs. The number of study participants in clinical trials ranged from 10 to 400 participants [11][12][13]. Two studies included patients with a preexisting condition, one included patients with type 2 diabetes mellitus and the other included patients with HIV [14,15].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 302 PubMed initial search results, 182 clinical trials (28,352 participants) met inclusion criteria and were included in the final analysis 6–186 . The PRISMA study selection process is detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Spirulina extracts have also shown novel, anti-microbial activity as well as anti-inflammatory properties that can treat mild to severe fungal infections such as onychomycosis [13], viral infections [14] and some effects on the microbiome [15].…”
Section: The Challenge In Chronic Disease: Targeting Multiple Target mentioning
confidence: 99%